GE_GERICHTE P/15636/2016 vom 28. Juni 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;ABUS DE CONFIANCE;PERSONNE PROCHE;MÉNAGE COMMUN;PLAINTE PÉNALE;DÉLAI | CPP.404.al2; CP.138.al1.ch4; CP.110.al2; CP.30.al1; CP.31; CPP.126.al2.leta; CPP.426.al2